PSYCHOLOGICAL POSSIBILITIES OF FORMING TOLERANCE IN FUTURE EDUCATORS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, the psychological nature of tolerance and the importance of the formation of tolerance in future pedagogues today, the institutional model of the formation of tolerance are highlighted.